A qualitative study on Iranian nurses' experiences and perspectives on how to provide safe care in clinical practice. (June 2013) - Vaismoradi, Mojtaba; Salsali, Mahvash; Turunen, Hannele; Bondas, Terese
Nurses are the healthcare providers who are well positioned to strengthen patient safety through providing safe care in clinical practice. The purpose of this study was to explore and describe the experiences and perspectives of Iranian nurses in relation to how to provide safe care in clinical practice. A qualitative design by using a content analysis approach was applied for the data gathering and analysis. After employing a purposive sampling to choose 16 bachelor's degree nurses working in the medical and surgical wards of a referral teaching hospital in an urban area of Iran, semi-structured interviews were conducted to collect data. During the data analysis, three main themes emerged: 'providing safe care as the patient's right', with the subthemes: 'feeling a personal commitment' and 'incorporating patients' feelings of safety into providing safe care', 'encouraging reciprocal accountability in healthcare professionals' and 'leadership commitment to safe care'. The findings suggest that educators should provide more information during nurses' education to focus on the moral duty to provide safe care. In addition, the provision of safe care needs the commitment and collaboration of all healthcare professionals, as well as the leadership of nursing for removing obstacles to nurses' efforts to making the healthcare system safer.